Edukasi dan Pemeriksaan Pediculus Humanus Capitis Pada Siswa TK Kusuma Mulya 12 Desa Sendang Kecamatan Banyakan Kabupaten Kediri - Shofi, Muh.; Munawaroh, Siti; Purnamasari, Vivien Dwi; Agusti Lukis, Prima (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2026)
Health problems in school-age children continue to be a major concern due to their impact on health quality and future development. Pediculosis capitis (head lice infestation) is a frequently encountered issue, strongly associated with inadequate personal hygiene, especially hair care. This condition, common in early childhood, causes intense itching, discomfort, and interferes with learning. Therefore, preventive measures through health education and direct screening are needed. This community service initiative aimed to improve students' knowledge of pediculosis capitis and identify infestation rates among students at Kusuma Mulya 12 Kindergarten, Sendang Village, Banyakan District, Kediri Regency. Methods included educational lectures, discussions, demonstrations, and direct scalp examinations. Evaluation utilized pretests and posttests to measure knowledge change, alongside visual inspection to determine infestation prevalence. Conducted in May 2024 with 50 students, the activity revealed low baseline knowledge. Post-intervention, a significant knowledge increase was achieved (95% posttest score). Screening identified a 36% infestation rate. In conclusion, combined education and examination effectively improved knowledge and enabled early detection of head lice. This program is expected to promote early adoption of clean and healthy living habits.